Improved photoelectric performance of all-inorganic perovskite through different additives for green light-emitting diodes. Issue 59 (25th October 2019) - Yang, Xianqi; Gu, Huaimin; Li, Shuti; Li, Jihang; Shi, Hengzhi; Zhang, Jinyuan; Liu, Nana; Liao, Zebing; Xu, Wenzhu; Tan, Yuan
Abstract : Improving the performance of all-inorganic CsPbBr3 –PEO–PVP-based LEDs with the structure of ITO/PEDOT:PSS/Perovskite/TPBI/LiF/Al. Abstract : The exceptional optical and electronic properties of all-inorganic cesium lead bromide (CsPbBr3 ) perovskite make it an ideal new optoelectronic material, but low surface coverage limits its performance. The morphological characteristics of thin films have a great influence on the performance of perovskite light emitting diodes, especially at low coverage, and an inhomogeneous surface will lead to current leakage. To tackle this problem, the widespread adoption of composite layers including polymers poly(ethylene oxide) (PEO) and organic insulating poly(vinylpyrrolidone) (PVP) and all-inorganic perovskites is an effective way to increase the surface coverage and uniformity of perovskite films and improve the performance of perovskite light emitting devices. In our work, the perovskite thin films are investigated by using PEO and PVP dual additives, and the optimized CsPbBr3 –PEO–PVP LED with maximum luminance, current efficiency, and external quantum efficiency of 2353 cd m −2 (at 7.2 V), 2.14 cd A −1 (at 6.5 V) and 0.85% (at 6.5 V) was obtained. This work indicates that the method of using additives is not only the key to enhancing the quality of perovskite thin film, but also the key to achieving a higher performance perovskite LED.